Atomically ordered non-precious Co3Ta intermetallic nanoparticles as high-performance catalysts for hydrazine electrooxidation - Guang Feng (Nature Portfolio, 2019)
Intermetallic nanoparticles comprised of early transition metals are attractive for fuel cell applications, but are generally limited to noble metal-based systems. Here, authors report non-precious early transition metal intermetallic nanoparticles with promising electrocatalytic performance for the hydrazine oxidation reaction.